Personal decision making process : the Singapore undergraduates' perspective. - Ho, Wei Chung. (2008)
In this project, we investigated how decision making processes vary for decisions that university students make. We also examined the differences in decision processes engaged in when a person makes his own decision as opposed to giving advice to others.